Design and Implementation of Two-phase Boost Inverter using Interleaved Method to Increase Output Current - Setiyawan, Fahrul Indra; Pratomo, Leonardus Heru (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2025)
The advancement of technology is rapidly evolving, particularly in the field of electronics, namely power electronics. One of the applications is the use of new and renewable energy. The converters required in new and renewable energy are inverters with good quality and performance. The step-down (buck) inverter is commonly used in this application. Different from the normal inverter, the step up (boost) inverter is proposed to be analyzed, simulated, and implemented in this paper. The proposed inverter uses a two-phase interleaved boost inverter (TP DC-AC IBI) consisting of a full bridge inverter and dual AC-AC interleaved boost converter. The inverter part always converts DC voltage to AC voltage, while the dual AC-AC interleaved boost converter part serves to increase the output voltage. The inverter consists of three arms: the first and second arms are controlled by Sinusoidal Pulse Width Modulation (SPWM) using 180° phase-shifted carrier signal, and the third arm is controlled by a zero-crossing detector.  Pulse Width Modulation (PWM) is used to control dual AC-AC interleaved boost converter. By combining this inverter with dual AC-AC interleaved boost converter, a new topology is created. This study specifically investigated the strategy to control this new topology using current controls. The actual current was obtained by installing an HX-10P current sensor on the output side. The output current was compared with the reference current, and the next stage was controlled using a proportional plus integral controller. The control signals output was modulated using SPWM signals on the inverter side and PWM at the AC-AC interleaved boost converter side to drive many power switches. To guarantee that the desired current control can always be achieved, the actual current and reference current must always match. The proportional plus integral controller was chosen due to its simplicity, high accuracy, and quick response time. The analysis involved verifying simulation tests using Power Simulator (PSIM) software. The hardware implementation was conducted in the laboratory and tested using standardized equipment. A couple of inductors were installed to reduce harmonic current on the output side and obtained THD of 3.3%, which according to the IEEE 519-2014, has met the standard as it was less than 5%. Thus, this new topology can be used in new and renewable energy for its good performance.